Resúmenes de novedades - Foro Internacional, Revista (Foro Internacional, 2024)
MICHAEL MANN, On Wars, New Haven, Yale University Press, 2023, 616 pp. ADAM J. BERINSKY, Political Rumors: Why We Accept Misinformation and How to Fight It, Princeton, New Jersey, Princeton University Press, 2023, 240 pp. PETER TRUBOWITZ y BRIAN BURGOON, Geopolitics and Democracy: The Western Liberal Order from Foundation to Fracture, Nueva York, Oxford University Press, 2023, 264 pp. ARIEL COLONOMOS, Pricing Lives: The Political Art of Measurement, Nueva York, Oxford University Press, 2023, 320 pp. DANIEL TINAJERO, La élite hacendaria y el problema tributario de México, Massachusetts, Ciudad de México, flacso México, 2023, 250 pp. IAN SHAPIRO, Uncommon Sense, New Haven, Yale University Press, 2024, 352 pp. GERARDO L. MUNCK y MARTÍN TANAKA, El pensamiento sociopolítico latinoamericano: Ciencias sociales e intelectuales en tiempos cambiantes, Buenos Aires, Prometeo Editorial, 2023, 474 pp. ANDRÉS TZEIMAN y DANILO ENRICO MARTUSCELLI (coords.), La crisis de la democracia en América Latina, Cambridge, Buenos Aires, clacso, 2024, 386 pp. DIRK KRUIJT y KEES KOONINGS (eds.), Latin American Military and Politics in the Twenty-first Century: A Cross-National Analysis, Nueva York, Routledge, 2023, 272 pp. PHILIP PETTIT, The State, Princeton, New Jersey, Princeton University Press, 2023, 376 pp.